2019
DOI: 10.1186/s13173-019-0087-5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding automated and human-based technical debt identification approaches-a two-phase study

Abstract: Context: The technical debt (TD) concept inspires the development of useful methods and tools that support TD identification and management. However, there is a lack of evidence on how different TD identification tools could be complementary and, also, how human-based identification compares with them. Objective: To understand how to effectively elicit TD from humans, to investigate several types of tools for TD identification, and to understand the developers' point of view about TD indicators and items repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Please note that we prepared a short workshop for the developers in order to present the technical debt metaphor and demonstrated the self-assessment process. We rely on the research findings, which state a connection between the identified technical debt items and the ownership of the source code [25]. The developers were asked to report the title, description, technical debt type and sub-type (closed selection), and assessed effort to mediate for every technical debt item.…”
Section: Methodsmentioning
confidence: 99%
“…Please note that we prepared a short workshop for the developers in order to present the technical debt metaphor and demonstrated the self-assessment process. We rely on the research findings, which state a connection between the identified technical debt items and the ownership of the source code [25]. The developers were asked to report the title, description, technical debt type and sub-type (closed selection), and assessed effort to mediate for every technical debt item.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, there is research for identifying tech debt in test automation and applying software design principles for test automation development. [75][76][77] The criteria for when and what to automate are decided by the factors eligibility, priority, cost, coverage, end user usage, quality, maintainability, and time. [78][79][80] Certainly, there are various impediments for automation, and the factors contributing to hindrance of a robust test automation suite are discussed in Reference 81.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Technical debt (TD) emerges from intentional shortcuts or even mistakes taken by software practitioners in their projects [1,2]. Incurring debt can bring short-term benefits, 2 usually in terms of high productivity, but also long-term drawbacks, making the software difficult to evolve [3,4,5]. By performing TD management activities, a software team can make TD items visible and under control, allowing it to balance benefits and drawbacks of debt presence [6].…”
Section: Introductionmentioning
confidence: 99%